Speckle reduction in ultrasound endoscopy using refraction based elevational angular compounding - Parastoo Afshari (Nature Portfolio, 2021)
Abstract Endoscopic ultrasonography (EUS) is a safe, real-time diagnostic and therapeutic tool. Speckle noise, inherent to ultrasonography, degrades the diagnostic precision of EUS. Elevational angular compounding (EAC) can provide real-time speckle noise reduction; however, EAC has never been applied to EUS because current implementations require costly and bulky arrays and are incompatible with the tight spatial constraints of hollow organs. Here we develop a radial implementation of a refraction-based elevational angular compounding technique (REACT) for EUS and demonstrate for the first time spatial compounding in a radial endoscopy. The proposed implementation was investigated in cylindrical phantoms and demonstrated superior suppression of ultrasound speckle noise and up to a two-fold improvement in signal- and contrast- ratios, compared to standard image processing techniques and averaging. The effect of elevational angular deflection on image fidelity was further investigated in a phantom with lymph node-like structures to determine the optimum elevational angular width for high speckle reduction efficiency while maintaining image fidelity. This study introduces REACT as a potential compact and low-cost solution to impart current radial echo-endoscopes with spatial compounding, which could enable accurate identification and precise sizing of lymph nodes in staging of gastrointestinal tract cancers.